Cholesterol assimilation and modulation of Lactobacillus plantarum L8 and lactobacillus Pentosus S1 on ATP binding cassette transporter genes against HT-29 intestinal cell lines / Athifah Ismail - Ismail, Athifah (2024)
Probiotics gives a new insight in treating hypercholesterolemia. Recent research found that probiotics such as Lactobacillus possess multiple health benefits including cholesterol assimilation in human body. Bile salt deconjugation, cellular cell binding and ability to modulate cholesterol transporter genes were proposed as underlying mechanisms for cholesterol lowering activity. Lactobacillus plantarum L8 and Lactobacillus pentosus S1 isolated from fermented fish food known as pekasam were assessed for their ability to deconjugate bile salt such as taurodeoxycholic acid (TDCA). To achieve this, L. Plantarum L8 and L pentosus S1 were tested for bile salt deconjugation through direct plating assay on de Mann, Rogosa, Sharpe (MRS) agar supplemented with TDCA. The result showed that both L. Plantarum L8 and L. Pentosus S1 did not deconjugate bile salt on selective agar which might be due to species specificity factor where only certain species able to deconjugate bile salt. Different stages of cell growths (Growing, resting and dead cells) of L. Plantarum L8 dan L. Pentosus S1 were also tested for their ability to reduce cholesterol in MRS broth supplemented with cholesterol. It was found only L. Plantarum L8 was able to assimilate cholesterol by 33%, 8% and 1% for growing, resting and dead cells respectively, while L. Pentosus S1 did not show any activity which might also be due to species specificity, a condition where only certain species possess cholesterol lowering property. Bacterial growth has also been observed to identify whether incorporation of cholesterol in MRS broth would affect the growth pattern of L. Plantarum L8 and L. Pentosus S1 and their correlation with cholesterol reduction. As the result, L. Plantarum L8 has higher doubling time and growth rate as compared to L. Pentosus S1. This explains the cholesterol removal activity of L. Plantarum L8 being higher than L. Pentosus S1. After 18 h of incubation, L. Plantarum L8 supplemented with cholesterol demonstrated a maintained growth rate up to 24 h as compared to its control (absence of cholesterol). For molecular approach, to evaluate probiotics effect on cholesterol transporter genes expressions in intestinal cells, HT-29 cells were treated with 24h cholesterol then incubated with L. Plantarum L8 and L. Pentosus S1 for 6h. Total RNA of treated HT-29 cells were extracted then converted to cdna through reverse transcription polymerase chain reaction (RT-PCR). Subsequently, cdna was further evaluated for transcription of NPC1L1 and SCARB1 gene, a key cholesterol transporters gene which involve in cholesterol metabolism by using qpcr analysis. L. Plantarum L8 was able to downregulate NPC1L1 and SCARB1 while L. Pentosus S1 was able to downregulate NPC1L1 only. Downregulation of both genes proceed to cholesterol reduction in HT-29 cells. In conclusion. L. Plantarum L8 and L. Pentosus S1 can reduce cholesterol level however L. Plantarum L8 has greater potential to act as cholesterol lowering agent. Both probiotics can be a new alternative to assist CVD prevention in future.